Problematizing leadership learning facilitation through a trickster archetype: An investigation into power and identity in liminal spaces. (October 2021) - Edwards, Gareth; Hawkins, Beverley; Sutherland, Neil
This study uses the archetype of a 'trickster' to reflect back on, and hence problematize, the role of the educator/facilitator identity in leadership learning. This is based on the view that a trickster is a permanent resident in liminal spaces and that these liminal spaces play an important role in leadership learning. Our approach was based on the reading of the trickster literature alongside reflective conversations on our own experiences of facilitation of leadership learning, development and education. We suggest that paying attention to the trickster tale draws attention to the romanticization of leadership development and its facilitation as based on a response to crisis that leads to a further enhancement of the leader as a hero. Hence, it also offers ways to problematize leadership learning by uncovering the shadow side of facilitation and underlying power relations. We therefore contribute by showing how, as facilitators, we can use the trickster archetype to think more critically, reflectively and reflexively about our role and practices as educators, in particular, the ethical and power-related issues. In our conclusions, we make recommendations for research, theory and practice and invite other facilitators to share with us their trickster tales.